2010
DOI: 10.1186/1477-7525-8-96
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled asthma: assessing quality of life and productivity of children and their caregivers using a cross-sectional Internet-based survey

Abstract: BackgroundResults of a national survey of asthmatic children that evaluated management goals established in 2004 by the National Asthma Education and Prevention Program (NAEPP) indicated that asthma symptom control fell short on nearly every goal.MethodsAn Internet-based survey was administered to adult caregivers of children aged 6-12 years with moderate to severe asthma. Asthma was categorized as uncontrolled when the caregiver reported pre-specified criteria for daytime symptoms, nighttime awakening, activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 23 publications
6
77
3
Order By: Relevance
“…The presence of a relation between the dimensions of Peds 4.0 and the sociodemographic and clinical parameters is an important finding as such instruments could be used in therapeutic evaluations (Upton et al, 2005;Ware, 1997;Dean et al, 2010). Our results are in contrast with other results that have failed to observe gender differences (Varni et al, 2007;Varni et al, 2003) or found fewer negative associations (Reinfjell et al, 2006;Villalonga-Olives et al, 2010).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The presence of a relation between the dimensions of Peds 4.0 and the sociodemographic and clinical parameters is an important finding as such instruments could be used in therapeutic evaluations (Upton et al, 2005;Ware, 1997;Dean et al, 2010). Our results are in contrast with other results that have failed to observe gender differences (Varni et al, 2007;Varni et al, 2003) or found fewer negative associations (Reinfjell et al, 2006;Villalonga-Olives et al, 2010).…”
Section: Discussioncontrasting
confidence: 56%
“…As expected, self-reported scores for overall HRQOL of cancer children were more impaired than those of healthy children (Eiser, Eiser, & Stride, 2005;Sung et al, 2009;Sandeberg, Johansson, Hagell, & Wettergren, 2010;Varni, Limbers, & Burwinkle, 2007). School functioning was most impacted by chronic health conditions, as reflected by the higher rates of school absences (Dean et al, 2010), and quit of school. It should be noted that 11.6% of Lebanese pediatric cancer were outside the school and at risk to be illiterate people.…”
Section: Cancer Childmentioning
confidence: 52%
See 1 more Smart Citation
“…While there are several questionnaires for assessing parental/caregiver's health related quality of life not directly related to asthma (Osman & Silverman, 1996), there is only one instrument to examine the specific impact of childhood asthma on parental/caregiver functioning: The Pediatric Asthma Caregiver's Quality of Life Questionnaire (PACQLQ) . Whereas some studies find no association between caregiver's health related quality of life and children's asthma symptoms (Annett et al, 2003), duration of asthma illness and asthma pre-treatment severity (Vila et al, 2003), other studies report that caregiver's and child's health related quality of life are significantly associated with each other (Dean et al, 2009(Dean et al, , 2010Garro, 2011;Halterman et al, 2004). Halterman et al (2004) find that higher symptom levels with regard to childhood asthma are associated with lower parental health related quality of life.…”
Section: Impact Of Children's Asthma On Caregiver's Health Related Qumentioning
confidence: 90%
“…Caregivers of asthmatic children appear to be more compromised in their resistance to stress, mood, emotional stability, amount of spare time and leisure activities (Garro, 2011). Caregivers of children with uncontrolled asthma report significantly higher absenteeism than their controlled counterparts (Dean et al, 2009(Dean et al, , 2010. Both caregiver's health related quality of life, caregiver's perception of the child's asthma symptoms, and the child's health related quality of life may be important in diagnosis and control of established asthma in childhood (Skoner, 2002).…”
Section: Impact Of Children's Asthma On Caregiver's Health Related Qumentioning
confidence: 99%